2012
DOI: 10.18860/egalita.v0i0.2122
|View full text |Cite
|
Sign up to set email alerts
|

Peran Ibu Menyusui Yang Bekerja Dalam Pemberian Asi Eksklusif Bagi Bayinya

Abstract: <p>Exclusive breastfeeding is defined as an infant’s consumption of human milk without complementary foods for the first six months of life. Breastfeeding has many benefits and advantages for infants. Breast milk suffice infant’s necessary for energy, protein, vitamin and mineral. In addition, breast milk protect infants from susceptibility to infectious disease. Increase vulnerability to nutritional problems in infants recently due to the replacement of breast milk with formula milk in a manner and amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
3
0
7
Order By: Relevance
“…World Health Organization (WHO) merekomendasikan agar bayi baru lahir mendapatkan ASI eksklusif selama enam bulan sebab ASI adalah nutrisi terbaik bagi bayi dengan kandungan gizi paling sesuai untuk pertumbuhan optimal (Susanti, 2012). Namun pada kenyataannya, ASI eksklusif mengalami penurunan setiap tahunnya.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…World Health Organization (WHO) merekomendasikan agar bayi baru lahir mendapatkan ASI eksklusif selama enam bulan sebab ASI adalah nutrisi terbaik bagi bayi dengan kandungan gizi paling sesuai untuk pertumbuhan optimal (Susanti, 2012). Namun pada kenyataannya, ASI eksklusif mengalami penurunan setiap tahunnya.…”
Section: Pendahuluanunclassified
“…Hasil Penelitian ini juga menjelaskan sebanyak 24 responden (80%) bekerja sebagai ibu rumah tangga (IRT). Susanti (2012) Hasil uji statistik bivariat antara pijat oksitosin dengan pengeluaran ASI diperoleh nilai sigp= 0,025 (< 0,05). Hasil tersebut menunjukkan bahwa terdapat korelasi atau hubungan antara pijat oksitosin dengan pengeluaran ASI pada ibu pospartum primipara di Kota Singkawang.…”
Section: Hasil Danunclassified
“…A woman who works has the potential to be pregnant, have given birth, and/or lactating. These statistics are further reinforced by the results of a study by Susanti (2011) who showed that 70% of breastfeeding mothers in Indonesia are also working.…”
Section: Introductionmentioning
confidence: 89%
“…Kebutuhan nutrisi ini sebagian besar dapat terpenuhi dengan pemberian ASI yang cukup. ASI tidak hanya sebagai sumber energi utama tapi juga sebagai sumber protein, vitamin dan mineral utama bagi bayi,manfaat pemberiaan ASI ekslusif untuk bayi,ibu dan negra (Susanti, 2012 ;Widiyanto, 2012).…”
Section: Pendahuluanunclassified